Secular Versus Biblical Leadership Models: Hermeneutical Implication of Mark 10:41-45 for Contemporary Christian Ministers - Okunoye, Job Oluremi; Jemiriye, Oluwafemi Tolulope (Jurnal Ilmiah Tafsir Alkitab, 2025)
The passage of Mark 10:41-45 is a major discourse on leadership by Jesus Christ, contrasting secular notions of authority with the principles of servant leadership within Christian ministry. Scholars have worked on leadership and church governance related issues examining pastoral authority, leadership styles and propounded theories on leadership. But these scholars have not looked into the hermeneutical implications of this passage for contemporary Christian ministers who navigate dual roles in both secular and church settings. Through an exegetical analysis of Mark 10:41-45, this study examines Jesus' teachings on the nature of leadership, emphasizing humility, service, and sacrificial love as foundational to Christian leadership. Delineating between secular leadership models and biblical principles, this research offers insights into how Christian ministers can integrate these principles into their roles, fostering ethical leadership and enhancing the witness of the church in society. Quintessentially, this research underscores the enduring relevance of Jesus' teachings on servant leadership, advocating for a holistic approach that aligns biblical wisdom with contemporary leadership practices.